Virtual Reality Exposure Therapy: An Effective Solution for Military Personnel with PTSD - Irene, Fosu-Apraku; Lee, Yan Yan; Noll, Tamara; Zhao, Sally (Université d'Ottawa | University of Ottawa, 2015)
Background: Post traumatic stress disorder (PTSD) is a chronic, debilitating, psychological condition that occurs in a subset of individuals who experienced or witnessed life-threatening events [1]. Higher levels of PTSD are found among veteran populations [2] .Virtual reality exposure therapy (VRET) has been identified as an effective treatment for PTSD because it facilitates emotional engagement and intervention with the patients’ traumatic memory [3]. Purpose/Objectives: This review aims to examine the effects of VRET on military personnel diagnosed with PTSD. The purpose of this study is to determine whether VRET, as an emerging method of treatment, is effective at decreasing PTSD symptoms. Methods: A structured literature review was conducted to analyze the effectiveness of VRET as treatment for PTSD in military personnel. Peer-reviewed, English-only, studies were obtained from the Academic Search Complete database and assessed for quality and relevance before inclusion. The following keywords were used:  “military,” “post traumatic stress disorder,” and “exposure therapy.”   Results: The initial literature search results produced 43 peer reviewed articles. 8 articles met the inclusion criteria as they directly related to the population, intervention and outcomes under study. All 8 studies found VRET to have a statistically significant effect on PTSD symptoms.    Conclusions: The literature shows limited evidence on the effectiveness of VRET for the treatment of PTSD. Further research is needed with larger sample sizes to demonstrate its efficacy towards treating PTSD.